Discrimination Behind Nest and Nnest Dichotomy in ELT Pofesionalism - Fithriani, R (KnE Social Sciences, 2018)
This paper argues that the dichotomy between native English-speaking teachers (NESTs) and non-native English-speaking teachers (NNESTs) has resulted in discriminatory practices in English language teaching (ELT) professionalism. Reviewing four studies investigating discrimination in ELT industry in some Asian countries, this literature review reveals that most English as a foreign/second language (EFL/ESL) institutions give preferential treatment to NESTs based on some factors. Nativeness and nationality are among the top factors of discrimination in English teaching positions. Discrepancy in required academic qualification and income also prove that NNESTs have always been discriminated and marginalized in ELT employment. Furthermore, it is also found that racist policy applied by some institutions recruiting White English teachers solely because of their race and privilege. Finally, it can be concluded that some governments and institutions’ policies in recruiting English teachers have played a big role in perpetuating this discrimination against NNESTs by maintaining the ideology of NESTs as superior teachers in theories and practices of ELT. Keywords: Discrimination, native speakerism, ELT professionalism